Antigen-Presenting Cell-Like Neutrophils Foster T Cell Response in Hyperlipidemic Patients and Atherosclerotic Mice - Zhao, Tingrui; Jiang, Qingsong; Li, Wenming; Wang, Yin; Zou, Yao; Chai, Xinyu; Yuan, Zhiyi; Ma, Limei; Yu, Ruihong; Deng, Tao; Yu, Chao; Wang, Tingting (Frontiers in Immunology, 2022)
Neutrophils constitute abundant cellular components in atherosclerotic plagues. Most of the current studies are focused on the roles of granular proteins released by neutrophils in atherosclerosis. Here, we revealed a unique subset of neutrophils which exhibit the characteristics of antigen-presenting cell (APC) (which were called APC-like neutrophils afterwards) in atherosclerosis. The roles of APC-like neutrophils and relevant mechanisms were investigated in hyperlipidemic patients and atherosclerotic mice. Higher percentages of neutrophils and APC-like neutrophils were found in peripheral blood of hyperlipidemic patients than that of healthy donors. Meanwhile, we also identified higher infiltration of neutrophils and APC-like neutrophils in atherosclerotic mice. Ox-LDL induced PMA-activated neutrophils to acquire the APC-like phenotype. Importantly, upon over-expression of APC-like markers, neutrophils acquired APC functions to promote the proliferation and interferon-γ production of CD3+ T cells via HLA-DR/CD80/CD86. In accordance with what found in vitro, positive correlation between neutrophils and CD3+ T cells was observed in hyperlipidemic patients. In conclusion, our work identifies a proinflammatory neutrophil subset in both hyperlipidemic patients and atherosclerotic mice. This unique phenotype of neutrophils could activate the adaptive immune response to promote atherosclerosis progression. Thus, this neutrophil subset may be a new target for immunotherapy of atherosclerosis.